Endoscopic Repair of Type 1 Laryngeal Clefts and Deep Interarytenoid Notches: Cold Steel Versus Laser. (29th June 2021) - Kou, Yann‐Fuu; Kavoosi, Tazheh; Redmann, Andrew; Manning, Amy; Tabangin, Meredith; Myer, Charles M.; Hart, Catherine K.; Rutter, Michael J.; de Alarcon, Alessandro
Abstract : Objectives/Hypothesis: Endoscopic repair is the preferred surgical treatment for type 1 laryngeal clefts (T1LCs) and deep interarytenoid notches (DINs). No studies exist showing differences in repair rates using laser and cold steel. Our objective is to assess overall success and revision rate for endoscopic cleft repair and determine whether there is any difference in surgical outcomes between cold steel and laser techniques. Study Design: Retrospective chart review, cohort study. Methods: Retrospective review at a quaternary care pediatric hospital. Included all patients who underwent endoscopic repair for T1LCs and DINs between January 2010 and December 2019. Demographics, comorbidities, surgical data, outcomes, and revision status were collected and analyzed. We excluded patients who did not have a follow‐up at our institution. Results: A total of 194 patients were identified, 14 were excluded for lack of follow‐up data so 180 were analyzed. Of these, 127 had cold steel repair and 53 had laser repair. There is no significant difference in demographics or comorbidities. In the cold steel group, 4 of 127 (3.1%) had breakdown and in the laser group, 10 of 53 (18.9%) had breakdown. Patients who failed after a cold steel repair tended to break down later (median 12.7 months) when compared to laser repairs (median 2.1 months). Nine of the 10 patients with breakdown after laser repair were noted on initial postoperative evaluation. Conclusions: Endoscopic cleft repair is a well‐described and effective method for repair of T1LCs and DINs. Both cold steel and laser have high success rates; however, higher failure rates were noted in the laser repair group. Failure after laser repair may occur earlier than failure after cold steel repair. But this did not reach significance. Level of Evidence: 3 Laryngoscope, 131:2805–2810, 2021